1971
DOI: 10.1017/s0022112071001745
|View full text |Cite
|
Sign up to set email alerts
|

Orderly structure in jet turbulence

Abstract: Past evidence suggests that a large-scale orderly pattern may exist in the noiseproducing region of a jet. Using several methods to visualize the flow of round subsonic jets, we watched the evolution of orderly flow with advancing Reynolds number. As the Reynolds number increases from order 102 to 103, the instability of the jet evolves from a sinusoid to a helix, and finally to a train of axisymmetric waves. At a Reynolds number around 104, the boundary layer of the jet is thin, and two kinds of axisymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
755
5
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,911 publications
(838 citation statements)
references
References 29 publications
71
755
5
7
Order By: Relevance
“…The constant of proportionality in the fully developed region for the nondimensionalized mass flow rate was estimated to be 0.32 by Ricou & Spalding (1961). ( The experimental results of Falcone & Cataldo (2003) and Crow and Champagne (1971) found c to be 0.297 and 0.292, respectively. The entrainment rate of the jet (c = dm/dx) decreases as the Reynolds number increases.…”
Section: Turbulent Jetsmentioning
confidence: 98%
“…The constant of proportionality in the fully developed region for the nondimensionalized mass flow rate was estimated to be 0.32 by Ricou & Spalding (1961). ( The experimental results of Falcone & Cataldo (2003) and Crow and Champagne (1971) found c to be 0.297 and 0.292, respectively. The entrainment rate of the jet (c = dm/dx) decreases as the Reynolds number increases.…”
Section: Turbulent Jetsmentioning
confidence: 98%
“…The round jet is a widely studied canonical turbulent free-shear flow, [20][21][22][23] as it is relatively simple to set up experimentally and exhibits self-similar statistical structure, evolving downstream at a constant Reynolds number. An analytical solution of the boundary layer approximation to the incompressible turbulent jet mean momentum equations also exists.…”
Section: B Turbulent Jetmentioning
confidence: 99%
“…The value of 0.3 is in tune with the most preferred mode (i.e. the most amplified mode obtained by an artificial external excitation) according to Crow and Champagne [17]. Moreover, Cho et al [30] observed a non-pairing advection of vortices for higher Strouhal number from 0.6 to 0.9.…”
Section: Introductionmentioning
confidence: 64%
“…The highest sensitivity of round jets to excitation (i.e. the most amplified mode under small artificial excitations) is known be at the most preferred mode, at Strouhal number of 0.3-0.35 [17]. As mentioned above, the situation in annular jets is governed by two scales, e.g., Strouhal numbers for intermediate merging zone of the outer mixing region of annular jets are comparable or slightly smaller than those of jets, a very gradual decrease around 0.35 was presented, e.g., by Chan and Ko [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation